Bank Diversification Effects on Bank Performance and Risk Profile of Bank in Indonesia - Anthony Lukmawijaya; Sung Suk Kim (Universitas Pelita Harapan, 2015)
We investigate the relationship of Indonesian bank diversification towards its long term performance and risk profile with Indonesian bank data from 2009 to 2013. Non-interest income to total operating income of the bank measures its bank diversification level. Bank value is measured by the adjusted Tobin's Q and risk profile which is broken down into total risk, idiosyncratic risk, and systematic risk. The result shows that bank non-interest income diversification has a positive influence on its franchise value. There is, however, no strong evidence that diversification can lower a bank's risk profile.